SCIENTIFIC APTITUDE AND INTELLIGENCE AS CORRELATES OF PERFORMANCE OF STUDENTS IN PRE MEDICAL ENTRANCE TEST - Kaur, Navneet (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Scientific aptitude is construct of interacting hereditary and environmental determinants producing predispositions or abilities. We can identify to an extent, certain, not all, characteristics possessed by individual who succeed later in scientific endeavor. Scientific aptitude in necessary for pupils to pursue science education. Without having sizable amount of scientific aptitude, one cannot have science education properly, and of course even one cannot adjust in the daily life. It helps in improving the performance of the child in competition examination. So every student of medical stream should possess good scientific aptitude.